Studi Sistem Dispersi Padat Isoxsuprine Hcl Povidon K-30 - Taslim, Tuty; Halim, Auzal; Suardi, Muslim (Fakultas Farmasi Universitas Andalas, 2010)
A study on Solid Dispersion System of Isoxsuprine HCl by using syntetic polymer Povidon K-30 to increase solubility has been done has been done. The solid dispersion system were prepared by using solvent method with any comparison ( Taslim, 2007). Charactheristics of physical chemistry properties of solid dispersion such as dissolution test, X-ray diffraction analysis, Differential Scanning Calorimetry, and Fourier Transform Infra Red were assayed. The dissolution test from solid dispersion by using UV spectrophotometer. Statistical analysis of solid dispersionâs dissolution test was done by using Anova. The characteristic X-rayâs diffraction and FTIR showed that solid dispersion with drug to polimer ratio of 1:9 ; 2:8 ; 3:7 were amorf in comparison to other solid dispersions. Statistical analysis by one direction Anova concluded that the dissolution profile of the solid dispersion system of 2:8 was the highest.